2019
DOI: 10.1021/acs.energyfuels.9b01983
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Removal Efficiency of Low-Partial-Pressure H2S in a Tetramethylammonium Glycinate Activated N-Methyldiethanolamine Aqueous Solution

Abstract: The absorption performance including absorption capacity and loading values of low-partial-pressure H2S in tetramethylammonium glycinate ([N1111]­[Gly]) promoted N-methyldiethanolamine (MDEA) aqueous solution was measured. The apparent absorption rate was calculated from the time-dependent absorption capacity. The effects of absorbent composition, temperature, and H2S partial pressure on absorption capacity and apparent absorption rate were demonstrated. The H2S removal efficiency was verified in a tray tower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 89 publications
0
17
0
Order By: Relevance
“…However, based on the research results, PZ is a new carcinogen. Formation of alternative materials is needed . New blending absorbents have to be developed to remove acid gases as a substitute for MDEA/PZ.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, based on the research results, PZ is a new carcinogen. Formation of alternative materials is needed . New blending absorbents have to be developed to remove acid gases as a substitute for MDEA/PZ.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the absorption rate and the desorption amount of H 2 S at atmospheric pressure using the monoethanolamine/MDEA absorbent showed a 95% absorption performance . AAIL/MDEA absorbents were used to test the absorption performance of H 2 S to show superior commercial sorbents for desulfurization . Based on the previous studies, the study of blending amine absorbents for simultaneous absorption and regeneration of CO 2 and H 2 S is required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Watanabe [ 8 ] critically analyzed the aforementioned technologies for natural gas desulphurization, usually relying upon liquid absorption, slurry reactors and fixed-bed columns. Alkylamine absorbents for sour gases [ 9 ] are typically adopted in large facilities [ 10 ] and they are economically demanding for high operating costs [ 11 ], together with drawbacks related to limitations in the selectivity and progressive degradation of the liquid sorbent. Slurry reactors [ 12 ] allow a good solid-fluid material exchange at relatively low operating temperatures and may represent, even in terms of sorbent recovery, a valid alternative to fixed-bed reactors.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we used MDEA aqueous solutions promoted by two ILs, namely tetramethylammonium glycinate ([N 1111 ][Gly]) and tetramethylammonium arginate ([N 1111 ][Arg]), to explore the performances of such mixed solutions for absorbing H 2 S. The results showed that the two AAILs were superior to MEA in promoting the absorption of H 2 S by MDEA solution. Moreover, of these two promoters, the MDEA aqueous solutions promoted by [N 1111 ][Arg] exhibited the highest absorption capacity and absorption rate for low-concentration H 2 S. Therefore, [N 1111 ][Arg]-promoted MDEA aqueous solutions show commercial potential [ 12 , 25 ].…”
Section: Introductionmentioning
confidence: 99%